TOLERANSI BERAGAMA WARGA DESA TABUAN DAN HAUWEI KECAMATAN HALONG KABUPATEN BALANGAN (STUDI KEKERABATAN) - Muhammad Yusuf; Asikin Nor (ADISAM PUBLISHER, 2023)
Hauwei and Tabuan villages, with Islamic, Kaharingan and Buddhist familial relations, live in the same house under the principle of familial tolerance. The wedding event included halal food and special spoon plates. The picture above describes how they respect each other and uphold religious tolerance so that life can run harmoniously. This research use desciptive qualitative approach. The data for this research is the religious tolerance of Tabuan village residents, Halong sub-district, Balangan district (Kinship Study). Interpretative qualitative analysis method with classification, comparison and interpretation. The research results show that the religious tolerance of Tabuan and Hauwei villagers is contributed by kinship factors. Nuclear family relationships between siblings and between children and parents are still maintained even though they have different religions. There are even religious differences that occur when they live in the same house. If many of the nuclear families have different religions, especially considering the aspect of the extended family, then there is increasing evidence that kinship is an important factor that contributes to religious tolerance. These results prove that the kinship system is a mechanism that connects conjugal families (and individuals who do not live in families) in a way that influences the integration of the general social structure and increases the ability of society to reproduce itself in an orderly manner.